A construção do plano de desenvolvimento institucional no contexto do Instituto Federal de São Paulo: contributos à democratização da gestão pedagógica - Iadocicco, Fernanda Neves (2019)
The democratization of educational management is a key factor in ensuring community participation in school decisions, which contributes to the construction of a fair and quality education for all. In the elaboration of its Plano de Desenvolvimento Institucional (PDI) (Institutional Development Plan (IDP)), Higher Education Institutions and Federal Institutes of Education have the opportunity to experience a democratic process, bringing together all educational subjects in the definition of their mission and the strategies necessary for the achievement of their goals and objectives. This study aims to analyze the process of Federal Institute of São Paulo (IFSP) construction of the PDI (2014-2018), especially regarding its contributions to democratize the pedagogical management of the institution. The qualitative research is based consolidated through an institutional case study on a bibliographic analysis that explores theoretical approaches on the subject and a documental analysis, based on educational legislation and institutional documents, such as the Relatórios de Gestão (Management Reports) and the Plano de Desenvolvimento Institucional (Institutional Development Plan), being that for the data collection also questionnaires and interviews were used as investigative tools. As a result, the analysis of the pedagogical aspects indicated advances in the PDI/IFSP/2014-2018 elaboration, built collectively, contributing to the institutional democratization of the pedagogical management. However, there are challenges to improve this construction, where the incentive for greater community participation is essential for the local productive arrangements development and for the recognition of the needs and particularities of each region where the IFSP is installed. It is worth emphasizing the importance of pedagogical management democratization to meet the community demand and thus to form a citizen with specific abilities and competences to attend it, in this sense, it is concluded that the democracy and participation learning is something that must be lived continuously, in a constant exercise, within the context of the IFSP.